Mediascapes of Japanese Culture in Chinese Drama Series: Adaptations of Zhao Qianqian works - Fairuzzahra, Nabila Vina (Universitas Pendidikan Indonesia (Indonesia University of Education), 2020)
Globalization has encouraged the enhancement of media, so that various kinds of information are accessible. Hence, Japan is utilizing media to promote their pop culture globally. One of the countries whose media is influenced by Japanese pop culture is China. This study aims to determine the mediascapes of Japanese pop culture in Chinese drama series, specifically the ones that are adapted from Zhao Qianqian’s works; A Love So Beautiful (2017) and Put Your Head on Your Shoulder (2019). Theory used in this study is mediascapes–one of the five dimensions in Arjun Appadurai’s disjuncture globalization theory. The method of this research is descriptive analysis with qualitative approach. This study shows that mediascapes of Japanese pop culture can be identified through images of some anime characters that appear in A Love So Beautiful and Put Your Head on My Shoulder drama series. These images are shown to attract Chinese people’s interest of Japanese pop culture as well as to construct the idea of Japan’s positive image.